FRIENDSHIP RELATIONS BETWEEN AISYIYAH BOARDING SCHOOL BANDUNG STUDENTS - Muhammad Ridho Albari; Ghaida Az-zahra Kusnadi; Kamila Suci; Muhammad Fadilah Noor Agustian; Mamat Supriatna; Nandang Budiman (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
During adolescence, success in interacting with their social environment, especially with their peers, will greatly affect the process of their further psychological development. SMP Aisyiyah Boarding School Bandung is one example of a school that has its own specialty, therefore, this research entitled "Friendship Relations Between Aisyiyah Boarding School Bandung Students" to find out more about friendship relationships in girls' schools. In this research, the method that we use is to use a quantitative approach with a survey method, with a random sampling technique. The instrument used in this study was developed based on the definition of operational variables which were then compiled into a grid to reveal friendship relationships, which was adapted from a previous research instrument by Hasilah Rachman in 2010. The results of this study indicate that friendship relationships at SMP Aisyiyah Boarding School Bandung tend to be at a moderate level. It is hoped that this research can be used as a reference to find out how the ability of relations in a school is.